2016
DOI: 10.3390/app7010032
|View full text |Cite
|
Sign up to set email alerts
|

Autofluorescence Imaging and Spectroscopy of Human Lung Cancer

Abstract: Lung cancer is one of the most common cancers, with high mortality rate worldwide. Autofluorescence imaging and spectroscopy is a non-invasive, label-free, real-time technique for cancer detection. In this study, lung tissue sections excised from patients were detected by laser scan confocal microscopy and spectroscopy. The autofluorescence images demonstrated the cellular morphology and tissue structure, as well as the pathology of stained images. Based on the spectra study, it was found that the majority of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 55 publications
1
20
0
Order By: Relevance
“…The convolutional layer includes feature maps (depth slices) and each feature map includes sets of neurons. The output of the convolutional operation in a convolutional layer is given by Equation (2). In this equation, F is denoted as the kernel (filter) size, m is denoted as the feature maps, B is denoted as the bias, and the weight of a kernel is denoted as j W .…”
Section: Pooling Layer (Subsampling)mentioning
confidence: 99%
See 1 more Smart Citation
“…The convolutional layer includes feature maps (depth slices) and each feature map includes sets of neurons. The output of the convolutional operation in a convolutional layer is given by Equation (2). In this equation, F is denoted as the kernel (filter) size, m is denoted as the feature maps, B is denoted as the bias, and the weight of a kernel is denoted as j W .…”
Section: Pooling Layer (Subsampling)mentioning
confidence: 99%
“…With a death toll of over 70%, the American Cancer Society put lung cancer among the most aggressive cancers in 2016 [1]. Consequently, the probability of survival will be increased to 49% if the cancer is detected in the early stage when it is limited to the lung and has not spread out to the lymph [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies were further investigated on the native fluorescent fluorophores, such as reduced nicotinamide adenine dinucleotide (NADH), flavin adenine dinucleotide (FAD), collagen and porphyrins [20,21]. Porphyrin derivatives often show enhanced intensity in different cancers, including urinary cancer [23], lung cancer [9,24] and cervical cancer [25]. Collagen, the main structural protein in the extracellular space, links with breast cancer development and helps to form a picture of the chemical component in microenvironment within normal or diseased tissue [22].…”
mentioning
confidence: 99%
“…There has been some reports using native fluorescence spectroscopy for cervical cancer detection on blood samples [26,27], urine samples [27], animal models [28], cell lines [29,30], human cervical tissue sections [24,31,32] and in vivo by colposcopy [33]. Most of the studies reported the intensity difference between healthy and cancerous samples, but the sensitivities in the literature are variable, ranging from 62% to 92% [26,33].…”
mentioning
confidence: 99%
“…This imaging technique is noninvasive, label-free, and reveals 3D information due to intrinsic depth sectioning. The three imaging modalities provide complementary information: THG contrast originates from interfaces and inhomogeneities, revealing for example membranes of cells and their cell nuclei, and lipid bodies [5][6][7][8][9][10][11][12]; SHG contrast comes from noncentrosymmetric molecules, such as collagen fibers [13][14][15][16][17][18]; and MPEF contrast arises from autofluorescent molecules and structures, including cellular fluorophores such as flavin adenine dinucleotide (FAD), nicotinamide adenine dinucleotide (NADH) and extracellular fluorophores such as collagen and elastin fibers [19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%